Privacy Protection Based Secure Data Transaction Protocol for Smart Sensor Meter in Smart Grid - Woong Go; SeulKi Choi; Jin Kwak (International Journal of Distributed Sensor Networks, 2013)
A smart grid is a data communications network integrated with an electrical grid that collects and analyzes near-real-time data on power transmission, distribution, and consumption. Currently, smart grid systems are considered to be necessary for improving the monitoring and control of a power distribution infrastructure. Using distributed measurement architecture, it is possible to gather information about the smart grid status for monitoring and controlling the overall infrastructure, including remote units. This architecture can control the use of electricity. In particular, users can monitor and regulate the electricity consumption of each home appliance in real time. Likewise, power companies can monitor and control electricity consumption for stabilizing electricity supply. However, serious problems can arise in case of data leakage. For example, if malicious attackers can sniff and analyze data, they can obtain the usage pattern of a house and ascertain when it is empty. They could then burgle the house. We propose a privacy-enhanced secure data transaction protocol that can protect private data by encrypting them. The encrypted data include the user's ID, home appliance serial number, and electricity consumption. Thus, attackers cannot obtain important data from the encrypted data. In addition, unauthorized power companies cannot access this information too.